Claw the Giant Ape - Blade, Adam (Scholastic, 2008)
Searching for the pieces of the golden armor that he needs to rescue Aduro, Tom discovers the golden chain mail around the neck of Claw the Giant Ape and enters in a fierce battle with the monster, calling on Ferno the Fire Dragon for help.